ANCIENT AND CONTEMPORARY EDUCATIONAL SYSTEMS (SIGNIFICANCE OF PAST IN THE FORMATION OF FUTURE) - Gvelesiani, Irina (European Scientific Journal, ESJ, 2014)
“The right of education is recognized as a human right and is understood to establish an entitlement to education”. During the centuries different communities of the world strove to rear future generations via equipping them with appropriate knowledge and skills. Knowledge acquisition acquired primary importance even in the ancient – Greek and Roman – societies. Education was regarded as an essential component of a person’s identity in ancient Greece and the type of education a person received was based strongly on one’s social class and the culture of one’s polis. In contrast to the ancient times, knowledge acquisition has become a market-determined process during the last decades. It has undergone a significant expansion. However, the traces of old traditions can be seen within the walls of contemporary enlightment centers. The given paper draws parallel between the ancient and contemporary educational systems and outlines a significance of past in the formation of future.